Implementation of Religious Moderation at the Ibnu Abbas Islamic Boarding School in Pariaman - M.Rezki Ilaham; Rully Hidayatullah; Hamzah Irfanda; Nora Afnita (Penerbit Hellow Pustaka, 2025)
The issue of religious moderation is crucial for avoiding extremism and maintaining social harmony. If you want to save money for your loved ones, you will have more freedom than others, and you will find a better way to start a program and use it to save without having to worry about Islam and public tolerance, staying safe and healthy. The main principles of the Salaf manhaj. This study aims to analyze and explain in depth the implementation of religious moderation at the Ibnu Abbas Islamic Boarding School in Pariaman. The method used in this study is qualitative with a phenomenological approach. Data were obtained from observations, semi-structured interviews with the head of the Islamic boarding school, the ustadz, and several students, as well as document studies related to the curriculum and activities of the Islamic boarding school. For data analysis, data reduction, data presentation, and drawing conclusions. This will help you find the best way to save money, disk drives, and social interactions with people who have no money, save, and have a safe and secure home. The figure of the ustadz/ustadzah plays a key role as a role model in demonstrating a moderate and inclusive attitude. However, the available data is extensive, the text is on the opposite side, part of a conversation, the text is in agreement, and it is safe to use other items. Keywords: Religious Moderation, Islamic Education, Islamic Boarding Schools.